2000
DOI: 10.1209/epl/i2000-00219-7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of liquid tungsten studied by time-resolved photoelectron spectroscopy

Abstract: The electronic structure of liquid tungsten has been studied by time-resolved photoelectron spectroscopy on laser pulse molten surface layers. The valence band spectra reveal distinct changes of the electronic structure across the solid-liquid phase transition which are interpreted by marked changes of the short-range order on melting which change qualitatively the valence electron density of states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We refer to this as non-thermally assisted ultrafast melting due to the significant decrease in the melting temperature arising from changes in the empirical potential at elevated electronic temperatures. We note that Wahrenberg et al have observed the presence of a fcc-like liquid phase on the surface of laser irradiated tungsten from time-resolved photoelectron spectroscopy 66 .…”
Section: T-md Simulations Of Laser Irradiation Of W Thin Filmsmentioning
confidence: 65%
“…We refer to this as non-thermally assisted ultrafast melting due to the significant decrease in the melting temperature arising from changes in the empirical potential at elevated electronic temperatures. We note that Wahrenberg et al have observed the presence of a fcc-like liquid phase on the surface of laser irradiated tungsten from time-resolved photoelectron spectroscopy 66 .…”
Section: T-md Simulations Of Laser Irradiation Of W Thin Filmsmentioning
confidence: 65%
“…show changes in the DOS in the solid and liquid which reflect the changes in atomic ordering from bcc to a close-packed-like ordering [23][24][25].…”
Section: Molybdenummentioning
confidence: 99%
“…It has been established that these calculations can accurately determine the melting curve of nearly free electron metals, such as aluminium (Al) [24], where the interatomic forces remain relatively unchanged upon melting [17]. However, this is not the case of bcc transition metals, where the electronic structure is rearranged upon melting [17,25]. This different behaviour of bcc transition metals is quite significant for melting [17] and may be a possible cause for the large melting temperatures obtained from ab initio calculations, since these calculations does not take into account the free energy changes produced by the alterations of the delectron band of Mo upon melting.…”
mentioning
confidence: 99%